Strategy for Utilizing Artificial Intelligence in Islamic Religious Education Learning - Hamidah Ahmad; Ahdar Ahdar; Abdul Halik; Muh. Akib D; Ahmad Yani (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Strategy for Utilizing Artificial Intelligence in Islamic Religious Education Learning in Junior High SchoolsObjective: This study aims to develop strategies for the ethical and practical use of Artificial Intelligence (AI) features in the Canva application to transform Islamic Religious Education (IRE) learning at the junior high school level. Method: The research method used a qualitative descriptive approach. Data was collected through participatory observation, in-depth interviews, and document analysis. Results: Canva's Magic Studio and automation feature reduced material preparation time to 30–60 minutes, enabling the production of relevant visual media. The “SIKAP” blended learning model with strict Islamic content control increased student motivation, theological understanding, memory, classroom interaction, and pedagogical efficiency. Conclusion: The integration of Canva-based AI, which is ethical and strictly supervised by humans (human-in-the-loop), has proven capable of revitalizing junior high school PAI learning, making it more engaging and relevant to the digital generation without compromising Islamic values or the role of teachers as guardians of morals. Contribution: This study developed a replicable and low-cost “Blended PAI-AI with Islamic Content Control” model for PAI teachers in Indonesia. It enriched the TPACK theory with the dimensions of Islamic ethics and content validation in AI-assisted religious education.INDONESIOA: Strategi Pemanfaatan Kecerdasan Buatan dalam Pembelajaran PAI di SMPTujuan: Penelitian ini bertujuan mengembangkan strategi pemanfaatan fitur Kecerdasan Buatan (AI) pada aplikasi Canva secara etis dan efektif untuk mentransformasi pembelajaran Pendidikan Agama Islam (PAI) di jenjang SMP. Metode: Metode penelitian menggunakan pendekatan deskriptif kualitatif, Data dikumpulkan melalui observasi partisipatif, wawancara mendalam serta analisis dokumen. Hasil: Fitur Magic Studio dan otomatisasi Canva mengurangi waktu persiapan materi menjadi 30–60 menit, menghasilkan media visual relevan. Model blended learning “SIKAP” dengan kontrol konten Islami ketat meningkatkan motivasi siswa, pemahaman teologis, daya ingat, interaksi kelas, dan efisiensi pedagogis. Kesimpulan: Integrasi AI berbasis Canva yang etis dan diawasi ketat oleh manusia (human-in-the-loop) terbukti mampu merevitalisasi pembelajaran PAI jenjang SMP sehingga lebih menarik dan relevan bagi generasi digital tanpa mengorbankan nilai-nilai Islam maupun peran guru sebagai penjaga akhlak. Kontribusi: Penelitian ini mengembangkan model “Blended PAI-AI dengan Kontrol Konten Islami” yang mudah direplikasi dan berbiaya rendah untuk guru PAI di Indonesia, serta memperkaya teori TPACK dengan dimensi etika Islam dan validasi konten dalam pendidikan agama berbantuan AI.